2019
DOI: 10.2147/ott.s198421
|View full text |Cite
|
Sign up to set email alerts
|

<p>Clinical outcome of osteosarcoma and its correlation with programmed death-ligand 1 and T cell activation markers</p>

Abstract: Purpose Although both anti-PD-1 antibody and treatments using anti-PD-L1 antibody are currently in clinical use, their therapeutic effects vary according to cancer type. One of the factors accounting for this variability is the expression level of the immune checkpoint molecule that differs between cancer types; thus, it is important to clarify the relationship between clinical outcomes and immune checkpoint molecules for all types of human cancer. The purpose of this study is to evaluate the clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 33 publications
(35 reference statements)
0
22
1
Order By: Relevance
“…It has also been reported that a high level of PD-L1 predicts a reduced 5-year event-free survival in patients with OS, and is correlated with early metastasis [24,26]. We did not observe a significant difference in survival rates between PD-1-positive and -negative cases or PD-L1-positive and -negative cases.…”
Section: Discussioncontrasting
confidence: 46%
“…It has also been reported that a high level of PD-L1 predicts a reduced 5-year event-free survival in patients with OS, and is correlated with early metastasis [24,26]. We did not observe a significant difference in survival rates between PD-1-positive and -negative cases or PD-L1-positive and -negative cases.…”
Section: Discussioncontrasting
confidence: 46%
“…The existing poor prognosis of OS can be traced to tumor progression and recurrence, and this problem has resulted in a low 5-year survival rate for people diagnosed with bone cancer. 4 To improve the survival outcome of patients with OS, it is crucial to explore the molecular mechanism of OS progression.…”
Section: Introductionmentioning
confidence: 99%
“…In the clinical setting, PD-L1 expression is known to correlate with bad prognosis [ 79 ], and patients with higher levels of T-cell activation markers show good prognosis [ 80 ]. However, the phase 2 clinical trial using the anti-PD-1 antibody (Pembrolizumab) with sarcoma patients resulted in only one of the 22 patients with osteosarcoma having an objective response [ 81 ].…”
Section: Cancer Immune Therapy and Cancer Immunoeditingmentioning
confidence: 99%